2013
DOI: 10.1111/ejss.12021
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acidification of kaolinite and an Alfisol by aluminum oxides through electrical double‐layer interaction and coating

Abstract: Soil chemical properties are affected significantly by surface charge characteristics of the soil. Interaction between oppositely charged particles in variable‐charge soils plays an important role in variation of soil electrochemical properties. In this study, the effects of Al oxides on surface charge and acidity properties of kaolinite and an Alfisol during electrodialysis were investigated. The results indicated that Al oxides, when mixed into kaolinite or the Alfisol, decreased the effective cation exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…Another potential factor is the presence of SRO and free Al and Fe inorganic species in the B but not the E horizons (Table ). In the illuvial horizons, some of these reactive mineral phases could mask potential cation exchange sites through diffuse double layer overlapping and coating of phyllosilicates (Hendershot & Lavkulich, ; Oades, ; Li & Xu, ). In the E horizon, reactive Al and Fe minerals were not present in significant amounts and we can surmise that phyllosilicates retained their negative surface charge.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential factor is the presence of SRO and free Al and Fe inorganic species in the B but not the E horizons (Table ). In the illuvial horizons, some of these reactive mineral phases could mask potential cation exchange sites through diffuse double layer overlapping and coating of phyllosilicates (Hendershot & Lavkulich, ; Oades, ; Li & Xu, ). In the E horizon, reactive Al and Fe minerals were not present in significant amounts and we can surmise that phyllosilicates retained their negative surface charge.…”
Section: Discussionmentioning
confidence: 99%
“…Maiti et al [ 31 ] reported laterite pH values in the range of 7.0–7.2. Similarly, Li and Xu [ 68 ] found the pH of kaolinite in the acidic (5.3) range, which was slightly lower than the pH of the kaolinite used in this study. Moreover, most samples had pH values in the acidic range.…”
Section: Resultsmentioning
confidence: 48%
“…Hence, kaolinite has low CEC, and it is hard to swell or shrink, depending on the wetness or dryness of the soil (nonexpanding clay). In addition, the low negative charge density of kaolinite results in the leaching of base cations from soil [45].…”
Section: Kaolinitic Soilsmentioning
confidence: 99%